ANALISIS PRODUKSI DAN PENDAPATAN USAHATANI TALAS JEPANG DI DESA TINANGKUNG KECAMATAN TINANGKUNG SELATAN KABUPATEN BANGGAI KEPULAUAN - Arnilawati Laosa; Saiful Darman; Max Nur Alam (Agroland: Jurnal Ilmu-ilmu Pertanian, 2016)
Respondent samples of 20 people were determined through a census technique.  Data was analyzed using a multi linier regression of Cobb –Douglas and income analysis.  The results showed that the independent variables (Xi) simultaneously affect the dependent variable of taro production (Y) significantly.  The value of Fcounted was 234.743>Ftable (8.66) with coefficient of determination (R2) was 0.988 indicating that 98.8% of the fluctuation of taro production can be explained by such variables as land area (X1), seed number (X2), labor (X3), education level (X4) and farming experience (X5) while the remaining 1.2% can be explained by other variable not included in the model.  Those variables mentioned above are simultaneously affecting the taro production significantly.  The regression coefficients at the 5% α level of those variables are 0.360, 0.240, 0.248, 0.136, and 0.064, respectively.  The average production of the taro farming system was 4.370 kg/0.43 ha of wet taro equal to 10,162.79 kg/2.35 ha.  The average income of the farming system was IDR 13,124,575/0.43 ha equal to IDR 30,558,290.79/2.35 ha per growing season.  The R/C value was >1 suggesting that the taro farming system is feasible to be developed. Keywords: Japanese taro, Income, and Production Factor